2023
DOI: 10.1007/s10115-023-01851-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus prediction based on machine learning framework: a real-world case study in Egypt

Abstract: Prediction and classification of diseases are essential in medical science, as it attempts to immune the spread of the disease and discover the infected regions from the early stages. Machine learning (ML) approaches are commonly used for predicting and classifying diseases that are precisely utilized as an efficient tool for doctors and specialists. This paper proposes a prediction framework based on ML approaches to predict Hepatitis C Virus among healthcare workers in Egypt. We utilized real-world data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…This research focused on exploring key clinical indices of NCDs in asymptomatic individuals. The application of machine learning in disease prediction is now well-established for its immense potential in analyzing complex datasets and uncovering patterns that may elude human detection [27][28][29][30]. The investigation employed various machine learning algorithms to predict hyperglycemia to enable early identification of individuals at a particular risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This research focused on exploring key clinical indices of NCDs in asymptomatic individuals. The application of machine learning in disease prediction is now well-established for its immense potential in analyzing complex datasets and uncovering patterns that may elude human detection [27][28][29][30]. The investigation employed various machine learning algorithms to predict hyperglycemia to enable early identification of individuals at a particular risk of developing diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…H. Mamdouh et al [ 11 ] developed four machine learning models including naive Bayes (NB), RF, KNN, and Logistic Regression to predict hepatitis C with a dataset of 859 patients. The RF model reached the accuracy of 94.06% without and 94.88% with adjusting for the hyperparameter values of the RF classifier.…”
Section: Discussionmentioning
confidence: 99%
“…Nandipati et al [ 10 ] found that binary class labels had better performance than multiclass labels in their study, and achieved an accuracy of 54.56% using the RF model. Mamdouh et al [ 11 ] developed four machine learning models and found that the RF model had an accuracy of 94.06% without hyperparameter tuning and 94.88% with tuning. El-Salam et al [ 12 ] used multiple-classifier models and achieved accuracy rates ranging from 65.6% to 68.9%.…”
Section: Introductionmentioning
confidence: 99%
“…Te paper in [5] introduced a machine-learning framework for predicting the hepatitis C virus in Egyptian healthcare workers, showcasing improved accuracies after sequential forward selection (SFS). After hyperparameter tuning with only four features, the random forest (RF) classifer achieved 94.88% accuracy.…”
Section: Related Workmentioning
confidence: 99%